School based inclusive mentoring within the scope of an experiential learning model (IEM) for teacher education - and Yazici, Mahmut Serkan; Uzuner, Fatma Gül (Teaching and Teacher Education, 2024)
This research employed school-based Inclusive Experimental Monitoring (IEM) mentoring within the scope of Kolb's (1984) experiential learning model. This was used to support pre-service teachers, combined with their existing undergraduate education at a Turkish university. The study undertook a mixed research approach, using the pre- and post-test experimental group (n=11) and control group (n=11). Various quantitative and qualitative data collection tools were used, including a personal information form, scales, questionnaires, video recordings, and unstructured observation. The results indicate that IEM has several positive outcomes for self-efficacy in inclusive education and readiness for the teaching profession. However, the study did not find any substantial changes in attitudes towards individuals with special educational needs, despite some observed positive impacts. It is believed that integrating IEM into the entire undergraduate education process can lead to further development in this regard.
Keywords: Experiential learning; Inclusive education; Inclusive mentoring; Special needs; Teacher education